Developing Burdens in Caring for a Relative with a Cancer Diagnosis: A Qualitative Study of Lived Experiences of Family Caregivers in Saudi Arabia - Eman Halil Al Enazy; Seham Mansour Alyousef (Nursing Reports, 2025)
Background: Cancer is a worldwide public health issue that impacts individuals in many ways. Family caregivers (FCGs) play a crucial role in providing care for cancer patients; as a result, they face several challenges as caregivers that sometimes go unreported. Aim: The purpose of this study was to explore the lived experiences of family caregivers with a developing burden of caring for a relative with a cancer diagnosis in Saudi Arabia. Methods: A qualitative study employing thematic analysis was conducted with ten family caregivers recruited through purposive sampling from the Prince Sultan Military City Hospital’s oncology department. Semi-structured interviews were conducted from July to August 2023 until data saturation was achieved. Results: Ten family caregivers participated in the study. Four main themes emerged from the data: antecedents to the caregiving burden, attributes of the caregiving burden, consequences of the burden, and religion and beliefs. Across these four main themes, there were 12 sub-themes. Conclusions and Implications: Family caregivers are crucial in caring for and supporting cancer patients. Thus, it is essential to shed light on family caregivers, who often remain invisible as secondary patients in healthcare systems, to understand the factors associated with developing caregiver burden. Education and support for family caregivers may decrease the burden on the family caregiver, which can positively impact the whole family unit, including the relative with the cancer diagnosis.